Use of Game-Based Guidance to Increase Career Awareness of Street Children - Mufidah, Elia Firda (Universitas Islam Negeri Raden Intan Lampung, 2019)
Street children are still a problem that needs to be moved. There are still many street children who drop out of school and do not understand what is related to the work taken. Game-based tutoring is in accordance with guiding principles and games so that children can be interested in joining this service. This research method uses pretest-posttest one group pre-experimental design. This study aims to find out how to use this program. This program aims to increase awareness. The Wilcoxon Career Awareness Test Results were obtained by Asymp. Sig = 0.043. Asymp comparison. Sig = 0.043 <α = 0.05 then Ho is accepted and H1 is rejected. Associated with a significant priority on the career awareness scores of street children before the implementation of assistance based on street children's awareness planning. The results of this study are increased career awareness of street children